Online Laboratory Submission System, Trakanphuetphon District Health Service Network, Ubon Ratchathani Province - ทุมนันท์ นิติชัย (Journal of Health Science of Thailand, 2024)
This research is an action research based on the PAOR cycle of Kemmis and McTagart. The objective was to study the development and results of developing an online laboratory testing system between the host hospital and the subdistrict health promotion hospitals in Trakanphuetphon District Health Service Network, Ubon Ratchathani Province The research was conducted between October 2020 and September 2021. The sample group consisted of 35 public health officials in the Trakanphuetphon District Health Service Network. The tools used for data collection were a system development evaluation model for online submission of laboratory tests between the host hospital and the subdistrict health promotion hospitals in Trakanphuetphon District Health Service Network and a satisfaction assessment form on the use of the online system. Data were analyzed by using statistics, mean, standard deviation. It was found that executives and the working groups were satisfied with the system. There were a total of 5 questions based on the context of the problems of the network; and the satisfaction response was at high level for all of them.